Penentuan Durasi Pemberian Low-molecular-weight Heparin Secara Subkutan pada Pasien Sindroma Koroner Akut untuk Mengurangi Kejadian Dan Luas Memar: Determining the Duration of Subcutaneous Administration of Low-molecular-weight Heparin in Acute Coronary Syndrome Patients to Reduce the Incidence and Extent of Bruising - Emil Huriani; Dwi Novrianda (Fakultas Keperawatan Universitas Andalas, 2015)
Use of Low-Molecular-Weight Heparin (LMWH) administered subcutaneously has beenrecommended in the treatment of Acute Coronary Syndrome. But the side effects of administration of LMWH inthe form of bruises seen in 20.6% to 88.9% (de Campos, da Silva, Beck, Secoli & de Melo Lima, 2013). Pleasenote the duration of LMWH injections subcutaneously best that can be applied to the events and extensivebruising low. The purpose of this study was to identify differences in the incidence and extensive bruising after48 hours at the injection site LMWH subcutaneously in administration with a duration of 10 seconds with aduration of 20 seconds.This Quasi-experimental research with posttest only-Equivalent control group designwas conducted at Hospital Regional Heart Center Dr M Djamil Padang. The sample was 35 Acute CoronarySyndrome patients receiving LMWH therapy. The independent variable is the injection of LMWHsubcutaneously with a duration of 10 seconds and with a duration of 20 seconds while the dependent variablewas the incidence and extensive bruising at the injection area LMWH subcutaneously after 48 hours. The datawere analyzed descriptively and by using Mann-Whithney. The statistical significance level was set at p =0.05.The results showed 54.29% of respondents with a duration of 10 seconds bruised injection (2.86% had abig bruise) compared with 28.57% of the respondents with the injection of 20 seconds bruised (2.86% had a bigbruise). There are significant differences in the incidence and extensive bruising in both groups (p = 0.013).Injection duration 20 seconds can reduce the incidence and extensive bruising at the injection subcutaneouslyLMWH.